Board financial experience and efficiency-based earnings management in pre- and post-international financial reporting standards - Kweh, Qian Long; Nourani, Mohammad; Lu, Wen-Min; Ting, Irene Wei Kiong (World Scientific Publishing Co Pte Ltd, 2024)
The study examines whether the board of directors with financial experience can effectively constrain earnings management pre- and post-International Financial Reporting Standards (IFRS). For a large balanced panel dataset of Taiwanese electronics companies over 2007–2017, we replace returns on assets in an augmented modified Jones model with efficiency scores derived using data envelopment analysis (DEA). Using DEA as an innovative adaptation in the accrual-based earnings management model, we aim to provide an accurate measure of earnings management. The results of our panel estimated generalized least square (EGLS) regression models, which account for heteroskedasticity and auto-correlation problems, indicate that the proportion of board of directors with financial and/or accounting experiences reduces earnings management pre-IFRS. However, their ability turns weaker post-IFRS. Overall, this study thus not only has important theoretical significance in that a board of directors with financial experience might and might not curb earnings management but also has an important practical contribution to decision-makers in companies regarding the effectiveness of board financial experiences in the IFRS era.